TA'LÎM MAHÂRAH AL-QIRÂAH FÎ AL-ZÂWIYAH AL-ISLÂMIYAH AL-SALAFIYAH BI ACEH - Dhiauddin, Dhiauddin (Arabi : Journal of Arabic Studies, 2018)
This study aims to discuss the process and learning steps in Pesantren Az Zawiyah in Aceh. The method of this study was descriptive qualitative. This study found that the process of teaching reading was conducted in the following steps: the contents used the Arabic heritage books, and the activities reading used extended and analytical texts. Meanwhile, the implementation of the process of education were salutation, review, the preparation of blackboard and books, the books read by the teachers and then repeated by students, translation, discussion, and encourage the students and conclusion. The methods used by the teacher were the word method, the partial method, the analytical method, the grammar method and the translation. The tests used by the teacher in reading skills were: sound tests.